Bone structure and perfusion quantification of bone marrow edema pattern in the wrist of patients with rheumatoid arthritis: a multimodality study - Teruel, Jose R; Burghardt, Andrew J; Rivoire, Julien; Srikhum, Waraporn; Noworolski, Susan M; Link, Thomas M; Imboden, John B; Li, Xiaojuan (Journal of rheumatology, 2014)
To quantify bone structure and perfusion parameters in regions of bone marrow edema pattern (BMEP), non-edematous bone marrow (NBM), and pannus tissue areas in the wrists of patients with rheumatoid arthritis (RA) using 3-Tesla (3T) magnetic resonance imaging (MRI), and high resolution peripheral quantitative computed tomography (HR-pQCT). Sixteen subjects fulfilling American College of Rheumatology classification were imaged using a HR-pQCT system and a 3T MRI scanner with an 8-channel wrist coil. Coronal T2-weighted and dynamic contrast-enhanced (DCE-MRI) images were acquired. BMEP and pannus tissue areas were segmented semiautomatically in T2-weighted images. NBM areas were placed at a similar distance from the joint space as BMEP regions. MR and HR-pQCT images were registered, and bone variables were calculated within the BMEP and NBM regions. Perfusion parameters in BMEP, pannus tissue, and NBM regions were calculated based on the signal-time curve obtained from DCE-MRI. Eighteen BMEP areas were segmented, 15 of them presented proximal to pannus-filled erosions. Significant increases in bone density and trabecular thickness and number were observed in all BMEP regions compared to NMB (p < 0.05). Significantly elevated perfusion measures were observed in both BMEP and pannus tissue regions compared to NBM (p < 0.05). BMEP regions showed significantly increased bone density and structures as well as perfusion measures, suggesting bone remodeling and active inflammation. Combining MRI and HR-pQCT provides a powerful multimodality approach for understanding BMEP and erosions, and for potentially identifying novel imaging markers for disease progression in RA.